Thermal studies and bond quality assessment of aerogel filled BMI composite curved sandwich panels - Antonyraj Zion Raj (2016)
The application of sandwich panel as insulating medium in aerospace industries is increasing in recent years as high strength to weight ratio of the structure is mandatory. Many researches were performed on customized honeycomb core sandwich panels to examine its thermal and acoustic insulating behavior and the same was improved by filling the empty core cells with low thermal conducting material, such as, aerogel granules. This research reports on fabrication, quality assessment and thermal study on aerogel filled Glass Fiber Reinforced Bismalemide customized honeycomb core sandwich panel. A method to fabricate curved honeycomb core sandwich panel is discussed in this project. For assessing the bond quality at the core fill-face sheet interface, an active thermography technique is implemented. The bond quality between core fill and face sheet is characterized by the percentage rate of surface temperature dissipation at the bond area. The thermography technique adopts the principle of Pulsed Video Thermography method except the surface temperature dissipation rate is calculated using thermal images at known intervals of time instead of recording the thermal video. Thermal study on curved honeycomb sandwich panel is conducted to investigate its overall thermal insulation behavior. The thermal insulation capability of aerogel filled composite panel is exemplified by measuring the percentage of temperature loss through the thickness of the panel. A similar heat transfer study is performed on aerogel filled flat composite sandwich panels with different core thicknesses to scrutinize the effect of thickness on thermal insulation characteristics. The heat transfer study on aerogel filled BMI-GFRP sandwich panels evolved to a conclusion that the panel could insulate an average of 65% of temperature from thermally exposed surface to the other.